Pediatrician's Beliefs and Practices Around Rapid Infant Weight Gain: A Qualitative Study - Megan H. Pesch MD, MS; Kimberley J. Levitt MD; Phoebe Danziger MD; Kelly Orringer MD (SAGE Publishing, 2021)
Rapid infant weight gain is a risk factor for later obesity. The objective of this study was to examine primary care pediatricians' beliefs and practices around rapid infant weight gain. Primary care pediatricians (N = 16) participated in a semi-structured interview about infant growth. Interviews were transcribed, analyzed for themes using the grounded theory and the constant comparative method then reliably coded for the presence of each theme. Three themes were identified, pediatricians (1) are uncertain about the concept, definition, and implications of excessive or rapid infant weight gain (N = 16, 100%), (2) are more comfortable with management of inadequate versus excessive or rapid weight gain (N = 10, 62.5%), and (3) perceive the primary cause of excessive or rapid infant weight gain to be overfeeding (N = 10, 62.5%). In conclusion, pediatricians are uncertain about the concept, definition, management, and long-term risks of rapid infant weight gain. Interventions to increase awareness and pediatrician sense of competence in management of rapid infant weight gain are needed.